Implementation Strategy of the SOLISPARES Model for Developing Excellent Character and High Competence in Indonesian Air Force Personnel - Pallaguna, Anton (The Eastasouth Journal of Information System and Computer Science, 2025)
This study aims to examine the implementation strategy of the SOLISPARES Model in developing human resources of the Indonesian Air Force (IAF) to foster excellent character and high competence among personnel. The SOLISPARES Model integrates five core dimensions: Personal Excellence, Interpersonal Capital, Organizational Excellence, Communal Collaboration, and Everlasting Glory. Each dimension is embedded with essential values—such as honesty, trustworthiness, discipline, loyalty, justice, and continuous learning—that collectively build a holistic framework for character and competence development. Employing a qualitative research method with a case study approach, this research was conducted within IAF educational and training institutions. Data were gathered through in-depth interviews with key stakeholders, participatory observation, and analysis of official strategic documents. Findings reveal that successful implementation of the SOLISPARES Model is determined by visionary leadership, strong organizational policy support, structured mentoring, and a continuous evaluation system. The application of the model significantly improved personnel’s integrity, discipline, teamwork, and technical expertise. The study recommends institutionalizing the SOLISPARES Model into the IAF’s human resource development curriculum as a long-term strategy to enhance institutional competitiveness, operational readiness, and resilience in the face of modern defense challenges.